Sea-Anemone Toxin ATX-II Elicits A-Fiber-Dependent Pain and enhances resurgent and persistent sodium currents in large sensory neurons - Klinger, Alexandra Birgit; Carr, Richard (Molecular pain, 2012)
Background:Gain-of-function mutations of the nociceptive voltage-gated sodium channel Nav1.7 lead to inherited pain syndromes, such as paroxysmal extreme pain disorder (PEPD). One characteristic of these mutations is slowed fast-inactivation kinetics, which may give rise to resurgent sodium currents. It is long known that toxins from Anemonia sulcata, such as ATX-II, slow fast inactivation and skin contact for example during diving leads to various symptoms such as pain and itch. Here, we investigated if ATX-II induces resurgent currents in sensory neurons of the dorsal root ganglion (DRGs) and how this may translate into human sensations.Results:In large A-fiber related DRGs ATX-II (5 nM) enhances persistent and resurgent sodium currents, but failed to do so in small C-fiber linked DRGs when investigated using the whole-cell patch-clamp technique. Resurgent currents are thought to depend on the presence of the sodium channel ?4-subunit. Using RT-qPCR experiments, we show that small DRGs express significantly less ?4 mRNA than large sensory neurons. With the ?4-C-terminus peptide in the pipette solution, it was possible to evoke resurgent currents in small DRGs and in Nav1.7 or Nav1.6 expressing HEK293/N1E115 cells, which were enhanced by the presence of extracellular ATX-II. When injected into the skin of healthy volunteers, ATX-II induces painful and itch-like sensations which were abolished by mechanical nerve block. Increase in superficial blood flow of the skin, measured by Laser doppler imaging is limited to the injection site, so no axon reflex erythema as a correlate for C-fiber activation was detected.Conclusion:ATX-II enhances persistent and resurgent sodium currents in large diameter DRGs, whereas small DRGs depend on the addition of ?4-peptide to the pipette recording solution for ATX-II to affect resurgent currents. Mechanical A-fiber blockade abolishes all ATX-II effects in human skin (e.g. painful and itch-like paraesthesias), suggesting that it mediates its effects mainly via activation of A-fibers.